Brachial plexopathy - Satish V Khadilkar; Snehaldatta S Khade (Annals of Indian Academy of Neurology, 2013)
Brachial plexus injury can occur as a result of trauma, inflammation or malignancies, and associated complications. The current topic is concerned with various forms of brachial plexopathy, its clinical features, pathophysiology, imaging findings, and management. Idiopathic brachial neuritis (IBN), often preceded with antecedent events such as infection, commonly present with abruptonset painful asymmetric upper limb weakness with associated wasting around the shoulder girdle and arm muscles. Idiopathic hypertrophic brachial neuritis, a rare condition, is usually painless to begin with, unlike IBN. Hereditary neuralgic amyotrophy is an autosomal-dominant disorder characterized by repeated episodes of paralysis and sensory disturbances in an affected limb, which is preceded by severe pain. While the frequency of the episodes tends to decrease with age, affected individuals suffer from residual deficits. Neurogenic thoracic outlet syndrome affects the lower trunk of the brachial plexus. It is diagnosed on the basis of electrophysiology and is amenable to surgical intervention. Cancer-related brachial plexopathy may occur secondary to metastatic infiltration or radiation therapy. Traumatic brachial plexus injury is commonly encountered in neurology, orthopedic, and plastic surgery set-ups. Trauma may be a direct blow or traction or stretch injury. The prognosis depends on the extent and site of injury as well as the surgical expertise.